Portals to Knowledge: CD-ROM Encyclopaedias, with Specific Reference to Microsoft Encarta 99 Encyclopedia - Louw, Phillip Adriaan (Lexikos, 1999)
The close interaction between linguistics and lexicography over the last few decades has had many good effects, not least of which has been the development of a theoretical framework or metalexicography. However, this close link has had an unfortunate result: the marginalisation in the theoretical debate of nonlinguistic dictionaries and especially of the encyclopaedia. In this article, semantic, lexicographical and pragmatic motivations will be given for a renewed interest in encyclopaedias. The revolution caused by CD-ROM encyclopaedias and the benefits they hold for a large spectrum of users, will be the most important pragmatic motivations addressed. Microsoft Encarta 99 Encyclopedia will act as a guide for the exploration of the impact this revolution has had on the ideas of user-friendliness and dictionary accessibility. Finally, a future is envisioned in which the Internet will be the logical culmination of the ultimate potential of computers as accessible, user-friendly reference tools. Keywords: access structure; active cross-references; cd-rom encyclopaedia; dictionary accessibility; encyclopaedia; guide structures; inner access structure; inner search path; internet; linguistic dictionary; mediostructure; multimedia; nonlinguistic dictionary; outer access structure; outer search path; passive cross-referencing; user-friendliness